Botulinum Toxins in Medical and Cosmetic Dermatology - Margit Juhász; Anna-Marie Hosking; Natasha Mesinkovska (European Medical Journal, 2021)
Background: Botulinum toxin (BoNT), a bacterially produced neurotoxin, is a mainstay in the dermatologic armamentarium. Although BoNT is commonly used to treated rhytides associated with ageing, it can be employed for a variety of other cosmetic purposes and medical disorders. Objective: In this review, the authors aim to describe the multitude of uses for BoNT in the dermatologic field. Materials and Methods: This manuscript was designed as a retrospective review of the on- and off-label applications of BoNT in dermatology.Results: In addition to treatment of rhytides, BoNT has been shown to decrease rosacea, menopause-associated flushing, and facial sebum production, while improving patient confidence in their appearance. Furthermore, BoNT has been successfully used to treat primary hyperhidrosis, hair loss, aberrant scarring, Raynaud's phenomenon-associated vasospasm, as well as a variety of skin diseases. Side effects of BoNT include pain or discomfort associated with injections during treatment, bruising, asymmetry, and swelling. Patients are generally satisfied with clinical results after BoNT treatment. Conclusion: Dermatologists should be aware of all on- and off-label applications of BoNT to provide patients with timely and appropriate medical care. Further research must be completed to fully characterise the safety and use of BoNT for off-label purposes.